Effectiveness of Regional Regulation of Livestock Number 19 of 2007 concerning Maintenance and Control of Livestock (Study of Lawang Agung Village, Seluma Regency) (Fakultas Hukum Dehasen, 2021)
The purpose of this study was to determine the effectiveness of the Regional Regulation of Livestock Animals No. 19 of 2007 concerning the Maintenance and Control of Livestock. The research method used is Empirical Research, which is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior through direct observation. Empirical research is also used to observe the results of human behavior in the form of physical relics and archives. The effectiveness of the supervision of the Regional Regulation Number 19 of 2007 concerning the Maintenance and Control of Livestock is considered successful. Lack of public awareness in maintaining order in raising livestock.